Pollution to Pigment the Innovative Technology Turning Air Pollution into Ink - Bhushan.M. Chitte; Trunali L. Bramhane; Divya D. Pagar; Om A. Ghodke; J.K. Dhavan (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Air pollution is a major environmental concern, with particulate matter (PM) being a significant contributor. This study introduces an innovative technology that captures and converts PM into a sustainable pigment, transforming pollution into a valuable resource. The technology utilizes a proprietary process to collect PM from various sources, including diesel generators, industrial chimneys, and vehicular emissions. The captured PM is then processed into a range of pigments, including carbon black, iron oxide, and titanium dioxide. These pigments can be used in various applications, such as art supplies, cosmetics, and industrial coatings. This innovative technology offers a unique solution to mitigate air pollution while generating a valuable byproduct, promoting a circular economy and sustainable development.